Digital marketing and its potential contribution to positioning companies on the Facebook social network - Ortiz Coloma, Hernán Paúl; Pacheco Rodríguez, Franklin Rodrigo (SATHIRI, 2023)
The objective of the research was to propose a digital marketing strategy that contributes to the positioning of the Ambato fan page yesterday and today in the minds of the users. Different investigations were analyzed in order to design the strategy with the necessary tactics to gain space in the market, having as a basis the marketing 4p for the creation of the activities that will be used to increase the positioning. The research that is being carried out focuses on the qualitative aspect, with the objective of comprehending and explaining a specific reality or problem in an objective manner. To achieve this goal, the aim is to obtain measurements through the collection of documentary information, which would allow for the generalization of the results obtained. The methods used were: the documentary analysis and the field analysis by means of surveys carried out of the current clients, having as results the strengths of the page, because there is interaction between the users and it is also known the content of the information that is presented. The conclusion is that the success of positioning companies on the Facebook social network depends on the effectiveness of the information projected through digital marketing and strategies with current clients and potential clients to increase the communities among them and manage the predictions measured.